1996
DOI: 10.1111/j.1151-2916.1996.tb08980.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Grain Size, Phase Assemblage, and Mechanical Properties of 3 mol% Y‐TZP

Abstract: The effect of heat treatment on the grain size, phase assemblage, and mechanical properties of a 3 mol% Y‐TZP ceramic was investigated. Specimens were initially sintered for 2 h at 1450°C to near theoretical density; some specimens were then heat‐treated at 1550°, 1650°, 1750°, or 1850°C to coarsen the microstructure. The average grain size increased with heat treatment from <0.5 to ∼10 μ‐m. Phase analyses revealed predominantly tetragonal and cubic phases below 1750°C, with a significant decrease in tetragona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
105
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(131 citation statements)
references
References 26 publications
17
105
1
8
Order By: Relevance
“…Presence of cubic phase after sintering was already identified by some authors when sintering temperatures in the range of 1,450-1,600ºC were used 24,[31][32][33] . However, this phase is not always reported, mostly because of the overlap of the main planes of the cubic phase in relation to tetragonal 28) .…”
Section: Discussionmentioning
confidence: 99%
“…Presence of cubic phase after sintering was already identified by some authors when sintering temperatures in the range of 1,450-1,600ºC were used 24,[31][32][33] . However, this phase is not always reported, mostly because of the overlap of the main planes of the cubic phase in relation to tetragonal 28) .…”
Section: Discussionmentioning
confidence: 99%
“…As Ruiz and Readey have shown, only severe overfiring to grain sizes >1¯m can considerably increase the toughness of Y-TZP. 32) One question which has been arising during the interpretation of the phase composition in combination with fracture resistance data concerned the very high toughness of the materials sintered at low temperatures, especially when considering their moderate transformability. Possible sources of error might be overestimated toughness or underestimated transformability/transformation zone size values.…”
Section: Microstructurementioning
confidence: 99%
“…[53][54][55][56] Regarding the residual stress, and if it could be considered as a positive or negative attribute for zirconia after surface treatment, previous studies stated that the hump observed after cutting or surface grinding of TZP ceramics has been related to the formation of orthorhombic or rhombohedral phase 57,58 or lattice distortion. 59 Both of them resulted from the presence of residual stress.…”
Section: Discussionmentioning
confidence: 99%